Sistem Monitoring Dan Capture Recording CCTV - Fandi; Haryono, Wasis (CV. Shofanah Media Berkah, 2024)
This study aims to design and develop a CCTV Monitoring and Capture Recording System at PT Bali Towerindo Sentra Tbk. using the waterfall method. This system integrates access to various servers in one web-based application, which is designed to simplify and accelerate the process of taking DVR captures and increase reporting efficiency compared to previous manual methods. Features such as a centralized dashboard, data management (add, delete, update), and real-time access to CCTV recordings have successfully reduced redundancy and accelerated the workflow of related teams. The intuitive interface design and division of access rights between admin and user ensure that this system is easy to use without requiring intensive training. The implementation results show that this system improves data management efficiency, team productivity, and user flexibility in accessing information in real time.